PENERAPAN PEMBELAJARAN KOOPERATIF PADA MATERI RANGKAIAN LISTRIK TERHADAP HASIL BELAJAR SISWA DI MTS MATLA’UL-ANWAR - Aisyah, Aisyah; Ikhsannudin, Ikhsannudin; Regina, Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract :This research is to develop writing teaching material using Lesson study in learning procedure text. The method of this research Research and Development and the steps was adapted in form of Lesson Study. The Lesson Study consists of three steps; they are Plan, Do, and See. It includes some cycles to get the experience in improving the teaching learning process that should be better than before. Some teachers near the area have done this study to help the Seventh Grade Students in writing a procedure text at SMPN 3 Sungai Kakap. The aim was to produce the teaching materials which can improve the teaching learning process, especially in writing a procedure text. The improvement was concluded by analyzing the data from a writing test, observation sheet, field notes and questionnaires. This study was done in SMPN 3 Sungai Kakap from April to June 2015. The results showed there was a significant improvement of the students? ability in writing a procedure text by using the materials that had been developed in Lesson Study. Based on the experience in conducting this research, some recommendations were given to some schools and English teachers in Kabupaten Kubu Raya to produce the writing teaching materials using Lesson Study. Key words: lesson study, development research, producing teaching material.